Konseling Kontrasepsi Pada Masa Prenatal Dan Postnatal Terhadap Penggunaan Kontrasepsi Modern: Sistematik Literatur Review - Retno Heru Setyorini; Andina Vita Sutanto (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
The prenatal and postnatal periods require contraceptive counseling to increaseunderstanding of the benefits of contraception for reproductive health. The purpose of thisliterature review is to analyze the results of research related to the effectiveness of contraceptivecounseling carried out in the prenatal and postnatal periods to increase the use of moderncontraception. Writing this journal uses a literature study approach from several databases,namely PubMed, ProQuest and Google Scholar. Eight research journals reported thatinterventions in various forms and media led to better knowledge, more positive attitudes, andhigher intentions towards contraceptive uptake. The results of the study can be used as a sourceof information to help solve health problems, especially regarding decision making using moderncontraception.Keywords: Counseling, Family Planning, Contraception, Women of Childbearing Age